Nanoparticle-in-Microparticle Delivery Systems (NiMDS): Production, Administration Routes and Clinical Potential - Imperiale, Julieta Celeste (2013)
Microparticles (MPs) and nanoparticles (NPs) have received considerable attention for the design of drug delivery systems (DDS) with unique properties owing to the increased surface area and the ability to fine tune the release process. More recently, a new type of DDS that capitalize on the advantages of both NPs and MPs has been introduced. Nanoparticle-in-Microparticle Delivery Systems (NiMDS) comprise the encapsulation of NPs within MPs and lead to features that are unique and different from those of the individual components. These technology platforms can be produced employing from conventional to more sophisticated methodologies and equipment and they are administered by different routes such as oral, pulmonary or even parenteral. Moreover, if designed appropriately, they can (i) protect drug payloads and prevent physical and chemical instability phenomena in the biological environment, (ii) improve the release profile of the encapsulated agent, (iii) reduce or eliminate the burst effect and (iv) target specific cells, tissues and organs. The present review overviews the different approaches to produce NiMDS and discusses their potential implementation in clinics.